Vinculación a grupos armados: un resultado del conflicto armado en Colombia (2010)
This article begins with an historic summary of the conflict in Colombia, and the consequences of remaining in an armed group. It goes on to describe the reasons for the link in adults, in minor children and in women. At the end, the motivations for belonging to the armed forces are mentioned, finding several similarities between the reasons for the link to illegal armed groups in comparison to government armed forces.